1972
DOI: 10.1083/jcb.52.2.292
|View full text |Cite
|
Sign up to set email alerts
|

THE SYNTHESIS OF ACIDIC CHROMOSOMAL PROTEINS DURING THE CELL CYCLE OF HELA S-3 CELLS

Abstract: The synthesis and accumulation of acidic proteins in the tightly bound residual nuclear fraction goes on throughout the cell cycle of continuously dividing populations of HeLa S-3 cells ; however, during late GI there is an increased rate of synthesis and accumulation of these proteins which precedes the onset of DNA synthesis . Unlike that of the histones, whose synthesis is tightly coupled to DNA replication, the synthesis of acidic residual nuclear proteins is insensitive to inhibitors of DNA synthesis . So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(86 citation statements)
references
References 35 publications
3
83
0
Order By: Relevance
“…During cell development, the amount of this protein varies. For instance, biochemical (21,25,38) and cytochemical (4,5,34,36,46) data have shown that at the onset of DNA synthesis a considerable increase in nuclear nonhistone protein (NNHP) is noted. An increased NNHPDNA ratio is therefore usually found in proliferating tissue (28,301.…”
mentioning
confidence: 99%
“…During cell development, the amount of this protein varies. For instance, biochemical (21,25,38) and cytochemical (4,5,34,36,46) data have shown that at the onset of DNA synthesis a considerable increase in nuclear nonhistone protein (NNHP) is noted. An increased NNHPDNA ratio is therefore usually found in proliferating tissue (28,301.…”
mentioning
confidence: 99%
“…Synchrony was determined by ['~H]thymidine (New England Nuclear, Boston, Mass., 6.7 Ci/mmol) incorporation (20) and autoradiography (see Results). Ceils used for autoradiography were labeled with 10 /xCi/ml [3H]thymidine in suspension for 10 min, washed, resuspended in RSB, and fixed on slides with ethanol:chloroform:acetic acid (6:3:1).…”
Section: Cell Synchronization and Labelingmentioning
confidence: 99%
“…The synthesis of bulk chromosomal bound proteins goes on throughout the cell cycle (19) although some small proteins may be made only in S (6). These proteins showed different profiles on sodium dodecyl sulfate (SDS) gels depending on the cell cycle and changes in the rate of synthesis before DNA synthesis (20,2). Kolodny and Gross (10) analyzed total cytoplasmic proteins synthesized during the HeLa cell cycle on one-dimensional SDS gels and reported variations in certain proteins.…”
mentioning
confidence: 99%
“…Unless indicated otherwise, cells were grown for 1 day to 60 -70% confluency and treated with various concentrations of cadein1. Cells were synchronized at G 1 /S by a modified double thymidine block (15). For fluorescence-activated cell sorter analysis, cells were trypsinized, fixed with cold 70% ethanol (Ϫ20°C), treated with 100 g/ml RNase A (Sigma), and stained with 100 g/ml propidium iodide (Sigma).…”
Section: Methodsmentioning
confidence: 99%